Market Structure, Trade Liberalization and the GATS - Joseph Francois; Ian Wooton (Tinbergen Institute, 2000)
In this paper we examine the interaction between the different modesof market access commitments inservices (cross-border and establishment) market structure, andregulation. In this context, we focus on theimpact of improved domestic market access for a foreign serviceprovider on a domestic service market. Wework with a model where the domestic industry is assumed to beimperfectly competitive and, as a result ofdomestic regulation, able to act as a cartel. We also examine theincentives for the domestic firms toaccommodate the entry of the foreign firm by inviting it to join thecartel.
Keywords: F12; F13; F23; 330; services trade; trade liberalization; market access; imperfect competition; Dienstleistungshandel; Markteintritt; Handelsliberalisierung; Welt